Regional metamorphism and the alteration response of selected Silurian to Devonian mineral systems in the Nymagee area, Central Lachlan Orogen, New South Wales: a HyLogger™ case study - P. M. Downes; D. B. Tilley; J. A. Fitzherbert; M. E. Clissold (Australian Journal of Earth Sciences, 2016)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.